2022
DOI: 10.32604/cmc.2022.017910
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Cluster-Based Optimal Resource Management in IoT Environment

Abstract: Internet of Things (IoT) is a technological revolution that redefined communication and computation of modern era. IoT generally refers to a network of gadgets linked via wireless network and communicates via internet. Resource management, especially energy management, is a critical issue when designing IoT devices. Several studies reported that clustering and routing are energy efficient solutions for optimal management of resources in IoT environment. In this point of view, the current study devises a new En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Many researchers have paid attention to how to reduce energy dissipation for IoT devices due to limited energy resources by the battery [26]. Anchitaalagammai et al [27] have proposed efficient energy based on the clustering routing technique for resource management (EECBRM) in an IoT environment. Firstly, EECBRM employs the fuzzy logic method to group IoT devices (sensor nodes) in the network into clusters.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have paid attention to how to reduce energy dissipation for IoT devices due to limited energy resources by the battery [26]. Anchitaalagammai et al [27] have proposed efficient energy based on the clustering routing technique for resource management (EECBRM) in an IoT environment. Firstly, EECBRM employs the fuzzy logic method to group IoT devices (sensor nodes) in the network into clusters.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, network security is becoming a crucial research field, specifically after advancing transmission and Internet methods. It makes use of various tools like Network Intrusion Detection Systems (NIDSs) and firewalls for security purposes of assets and networks [7]. For monitoring the network traffic for suspicious and worse conduct permanently NIDSs are commonly utilized.…”
Section: Figure 1: Applications Of Iodmentioning
confidence: 99%
“…To further secure the tag, in 2004, Weis et al [6] suggested an access control method based on a random key's hash as its metaID. However, the tag may be monitored because the same metaID is used several times [7]. Randomized access control (RAC) was also proposed by Weis et al, which encrypts the ID of the tag with a random number.…”
Section: Literature Surveymentioning
confidence: 99%